2001
DOI: 10.3184/030823401103168587
|View full text |Cite
|
Sign up to set email alerts
|

Selective Preparation of Fluorescent 1,8-Naphthalimides using Acidic Alumina under Microwave Irradiation

Abstract: 7H-benzimidazo[2,1-a]benz [de]isoquinolin-7-one compounds were prepared in a selective manner by reaction between o-phenylenediamines and appropriate 1,8-naphthalenedicarboxylic anhydrides using acidic alumina under microwave irradiation.diamine (1 mmol) and acidic alumina (3g-Merck, 1078) were mixed with grinding. The mixture was irradiated in a 50 ml beaker in a microwave oven for the times indicated in Table 1. At the end of the irradiation, the reaction mixture was cooled to room temperature and extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…The 1 H‐NMR chemical shift and the integration values of the mixture of isomers suggest formation of almost an equimolar mixture of the two isomers. In an earlier report, it was suggested that similar reaction under microwave irradiation in the presence of alumina resulted only one isomer [12], but in our case we have failed to obtain pure isomer through the reaction condition described herein, and the isomeric product separation of 3 was not successful. However, the condensation reaction of 3‐nitro‐1,8‐naphthalic anhydride with 1,2‐diaminobenzene under solvothermal condition in acetic acid at 150°C in an autoclave gave only one isomer.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The 1 H‐NMR chemical shift and the integration values of the mixture of isomers suggest formation of almost an equimolar mixture of the two isomers. In an earlier report, it was suggested that similar reaction under microwave irradiation in the presence of alumina resulted only one isomer [12], but in our case we have failed to obtain pure isomer through the reaction condition described herein, and the isomeric product separation of 3 was not successful. However, the condensation reaction of 3‐nitro‐1,8‐naphthalic anhydride with 1,2‐diaminobenzene under solvothermal condition in acetic acid at 150°C in an autoclave gave only one isomer.…”
Section: Resultscontrasting
confidence: 57%
“…The compounds 2 and 4 are derived from a planar aromatic ring system, which is derived from 1,8‐naphthalic anhydride [6]. The imides derived from naphthalic anhydride are useful as fluorescence probes, and their applications are decided by the presence of tether connecting two similar or dissimilar molecules [12]. The compounds 2 and 4 have reasonable fluorescence emission properties on excitation at appropriate wavelengths.…”
Section: Resultsmentioning
confidence: 99%